From reconciliation to revolution: the Student Interracial Ministry, Liberal Christianity, and the Civil Rights Movement - Cline, David P. (University of North Carolina Press, 2016)
"Conceived at the same conference that produced the Student Nonviolent Coordinating Committee (SNCC), the Student Interracial Ministry (SIM) was a national organization devoted to dismantling Jim Crow while simultaneously advancing American churches' approach to race. In this book, David Cline details how, between the founding of SIM in 1960 and its dissolution at the end of the decade, the seminary students who created and ran the organization influenced hundreds of thousands of community members through its various racial reconciliation and economic justice projects"--